Effects of phosphorus deficiency on ion transport and its correlation with sugar content and anatomical structure in chickpea (Cicer arietinum L. cv. Bari chola-5) seedlings (Dhaka University Journal of Biological Sciences, 2014)
Phosphorus deficiency stimulated accumulation of Na+ in the root but declined in the shoot of chickpea seedlings. K+ content in the root and the shoot increased initially followed by a decrease. Phosphorus deficiency inhibited the accumulation of NO3?, PO43? and also sugar content both in the root and shoot. It also caused a decline in the accumulation of total sugar only in the root. The interrelationship between the effect of phosphorus deficiency on ion transport and anatomical structure was discussed. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20095 Dhaka Univ. J. Biol. Sci. 23(2): 157-164, 2014